Allium kuhrangense (Amaryllidaceae) a new species of Allium sect. Acanthoprason from Iran - Akhavan, Azadeh; Saeidi, Hojjatollah; Fritsch, Reinhard M. (Phytotaxa, 2014)
Allium kuhrangense, an endemic to Chaharmahal Bakhtiari province (Iran) is described here as a new species. This species grows on gravelly and rocky slopes of a mountainous region. It is morphologically most similar to A. austroiranicum and can be recognized as a member of the A. austroiranicum alliance. Allium kuhrangense is a diploid species with chromosome number of 2n = 2x = 16. Diagnostic characters, description, taxonomic comments, photographs and a distribution map of the new species as well as an identification key for the related taxa are provided. According to IUCN Red List Categories and Criteria, A. kuhrangense is assessed here as a “Critically Endangered” species.